2015
DOI: 10.1007/s00127-015-1039-9
|View full text |Cite
|
Sign up to set email alerts
|

Violence at work and depressive symptoms in primary health care teams: a cross-sectional study in Brazil

Abstract: Primary care workers presenting depressive symptoms and those who have experienced violence at work should be assisted. Policy makers should prioritize strategies to prevent these problems, since they can threaten primary care sustainability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
55
0
22

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(85 citation statements)
references
References 30 publications
8
55
0
22
Order By: Relevance
“…A strong relationship between WPV and depressive symptoms was well documented in many studies (da Silva et al., ; Roche, Diers, Duffield, & Catling‐Paull, ). Furthermore, WPV was regarded as a predictor of depressive symptoms (Montesó‐Curto et al., ) and WPV‐related distress might also lead to fatigue, burnout and leaving their job (Roche et al., ).…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…A strong relationship between WPV and depressive symptoms was well documented in many studies (da Silva et al., ; Roche, Diers, Duffield, & Catling‐Paull, ). Furthermore, WPV was regarded as a predictor of depressive symptoms (Montesó‐Curto et al., ) and WPV‐related distress might also lead to fatigue, burnout and leaving their job (Roche et al., ).…”
Section: Introductionmentioning
confidence: 66%
“…It was found that 36.3% of WPV victims presented intermediate depressive symptoms and 16% probably had major depression (da Silva et al., ). There were several studies attempting to recognize factors related to depressive symptoms among victimized nurses and related results were well documented (da Silva et al., ; Yu et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The subject, "workplace violence", has achieved prominence in the scientific community through studies conducted in different countries (1,5,6,9) and Estar em contato com o público (face a face); Falta de precisão na atribuição de papeis e responsabilidades; Falta de segurança no ambiente de trabalho; Instalações superlotadas; Longo tempo de espera por atendimento; Número reduzido de trabalhadores; Prestar assistência às pessoas com angústia, sua família e amigos; Trabalho isolado (sozinho); Outro(s). Qual(is)?___.…”
Section: Discussionunclassified
“…All forms of violence can be associated with depressive symptoms, (5) burnout, (6,7) minor psychiatric disorders, (6) low back pain (8) and a range of other psychological, physical, industrial, institutional and/or social impacts.…”
Section: Introductionmentioning
confidence: 99%
“…Egy kínai felmérésben 1404 közösségi ápolóból egy év alatt 51,6%-uk tapasztalt munkahelyi erőszakot, ezen belül érzelmi bántalmazást 46,23%, fenyegetést 23,08%, szó-beli szexuális zaklatást 10,54%, fizikai támadást 9,69%, szexuális támadást 4,34% szenvedett el [15]. Brazíliában 2943, alapellátásban dolgozó szakemberből 44,9% szenvedett el munkája során sértegetést, 24,8% fenyegetést, 2,3% fizikai agressziót, és 29,5% volt tanúja erőszaknak a munkahelyen [16]. 441 spanyol egészségügyi dolgozó közül 87,2% részesült sértegetésben és fenyegetésben, 83,6% fenyegető viselkedésben, 42% rángatásban [17].…”
Section: Agresszió Az Egészségügyi Dolgozók Körébenunclassified